2015
DOI: 10.1148/radiol.2015142948
|View full text |Cite
|
Sign up to set email alerts
|

Fractal Analysis of Myocardial Trabeculations in 2547 Study Participants: Multi-Ethnic Study of Atherosclerosis

Abstract: ).q RSNA, 2015 Purpose:To quantitatively determine the population variation and relationship of left ventricular (LV) trabeculation to LV function, structure, and clinical variables. Materials andMethods:This HIPAA-compliant multicenter study was approved by institutional review boards of participating centers. Results:Included were 2547 participants (mean age, 68.7 years 6 9.1 [standard deviation]; 1211 men). FD MaxApical are in arbitrary units. FD MaxApical reference ranges for BMI 30 kg/m 2 or greater (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 20 publications
2
58
1
1
Order By: Relevance
“…Amzulescu et al [15] divided their study group into tertiles but only for the purpose of survival analysis. In the MESA study, fractal analysis was performed on a non-heart failure population [1,24]. Surprisingly, unlike other authors, we found that patients with a high degree of trabeculation had better cardiac function and lower NT-proBNP.…”
Section: Discussioncontrasting
confidence: 72%
See 3 more Smart Citations
“…Amzulescu et al [15] divided their study group into tertiles but only for the purpose of survival analysis. In the MESA study, fractal analysis was performed on a non-heart failure population [1,24]. Surprisingly, unlike other authors, we found that patients with a high degree of trabeculation had better cardiac function and lower NT-proBNP.…”
Section: Discussioncontrasting
confidence: 72%
“…Possibly, this can be explained by the tertile study population allotment or by different study group characteristics. Our patient population was much younger with more severe heart failure symptoms compared to either Amzulescu's et al [15] or MESA's cohorts [24]. Some small studies suggested that noncompaction phenotype might indicate a more severe form of DCM [25].…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…The fractal signature of the adult human heart has been shown to differ by ethnicity, LV mass, coexistent hypertension, and increased body mass index (6). Cardiac MR fractal analysis is currently being used to understand the FD of the adult human heart at scale, in both the UK Biobank Study (n=100,000) and the US Multi-Ethnic Study of Atherosclerosis (MESA, >3,000).…”
Section: Trabecular Quantification Is Not Standardized a Variety Of mentioning
confidence: 99%